Pengaruh Brand Image dan Promosi Terhadap Keputusan Konsumen di Klub Betang Futsal Muara Teweh - Mtw, Tajeri (Sekolah Tinggi Ilmu Ekonomi Muara Teweh, 2020)
This study aims to determine the effect of brand image, promotion, influence of brand image and promotion together onconsumer decisions at the Club. Futsal Betang Muara Teweh The method used in this research is to use a descriptiveresearch form with quantitative data analysis. The population in this study was the consumers of Club Futsal MuaraTeweh, amounting to 370 people with a sample of 79 people. The data collection techniques used were observation andquestionnaire techniques. Data Analysis Techniques were performed with multiple linear regression tests. The results ofthe study concluded that there is an influence between brand image on consumer decisions at the Club Futsal BetangMuara Teweh, so to improve consumer decisions the company must pay attention to brand image. There is an influencebetween promotions on consumer decisions at the Club Futsal Betang Muara Teweh, so to improve consumer decisionsthe company must pay attention to promotions run by the company. There is an influence between brand image andpromotion together on consumer decisions at the Club Futsal Betang Muara Teweh, so to improve consumer decisionsthe company must pay attention to variables brand image and promotion.Further researchers suggested that the ClubFutsal Betang Muara Teweh always maintain the brand image company's in various ways including conductingactivities and social responsibility in the environment around the company and creating components that facilitate theintroduction of public targets to the company such as logos and slogans. Betang Futsal Club Muara Teweh whilemaintaining the performance of the company and further improved the company's performance, especially in services toconsumers. Betang Futsal Club Muara Teweh expected to increase promotional activities